Nickel oxide interlayer films from nickel formate–ethylenediamine precursor: influence of annealing on thin film properties and photovoltaic device performance1. Issue 20 (28th May 2015) - Steirer, K. X.; Richards, R. E.; Sigdel, A. K.; Garcia, A.; Ndione, P. F.; Hammond, S.; Baker, D.; Ratcliff, E. L.; Curtis, C.; Furtak, T.; Ginley, D. S.; Olson, D. C.; et al.
<x xml:space="preserve">Abstract</x> Decomposition/oxidation correlated to nanoscale c-AFM helps separate selectivity and conductivity.